Evalution of the perfect competititon in e-environment - Ensari, M. Şebnem (My University, 2003)
Bu çalışmanın amacı, e-ortamın tam rekabet varsayımlarıyla uyumunu değerlendirerek, e-ticaretin globalleşmeye etkilerini belirlemek, elektronik ortamın şu andaki ve gelecekteki durumunu incelemek, ve bu sistemin tam rekabete yol açıp açmadığını göstermektir. Bu amaca ulaşmak için, Tam Rekabet, Yeni Ekonomi ve E-ticaret konularında geniş bir literatür araştırması yapılmıştır. Tam Rekabetin Değerlendirilmesi, Globalleşme Trendi, Bilgi Teknolojisinde Devrim ve Elektronik ticaretin Makro Ekonomik yapıya etkileri bu kısımda incelenmektedir. Bu tezin araştırma aşamasında, e-ortamın tam rekabet piyasasına uyumu bilgisayar, yazılım, kitap ve hızlı tüketim pazarından toplam 60 adet firmadan elde edilen veriler yardımıyla incelenmiştir. Araştırma göstermektedir ki, tam rekabet ortamının varlığını ölçen boyutlar açısından sektörler arasında anlamlı bir farklılık vardır; e-ortamda kitap sektörü için sert fiyat rekabeti varken, bilgisayar ve yazılım fiyatları versiyonlama ve kişiselleştime stratejileri sayesinde değişkenlik gösterir. Ayrıca, farklı e-ticaret uygulamaları yapan firmalar arasında da tam rekabet ortamının varlığını ölçen boyutlar açısından anlamlı bir farklılık vardır. Örneğin, B2B şirketleri B2C şirketlerine göre daha karlıdırlar. Bütün bu bilgilerin ışığında, e-ortamda tam rekabet varsayımlarının ne ölçüde gerçek olduğu gösterilmektedir.

Objective of this study is to identify the effects of e-business on globalisation, to examine the current and possible future situations of e-economic environment and point out whether this process leads to perfect competition or not, by evaluating the harmony of perfect competition assumptions to the e-environment. In order to realise these objectives, an extensive literature survey about Perfect Competition, New Economy and E-commerce was conducted. The Evaluation of Perfect Competition, Trends towards Globalisation, the Revolution in Information Technology and the Impact of E-commerce to the Macro Economic Structure are examined in this part. In the research part of this thesis, the harmony of e-environment to perfectly competitive environment was investigated by data collected from 60 e-companies from computer, software, book and undurable goods sectors. The results indicate that there is significant difference in different sectors with respect to dimensions measuring the existence of the perfect competition environment; there is stiff price competition for book sector in the e-environment, whereas prices of computer and software industry differentiate with the help of versioning and customisation strategies. Additionally, there is significant difference in some of the dimensions between the companies with different e-business applications. For example, B2B companies are more profitable situation than B2C Companies. Under the light of these facts, it is shown to what extent the assumptions of perfect competition are realised within the e-environment.
Keywords: Elektronik Ticaret; Rekabet; Ticaret